Antiretroviral Therapy Concentrations Differ in Gut vs. Lymph Node Tissues and Are Associated With HIV Viral Transcription by a Novel RT-ddPCR Assay. (15th April 2020) - Lee, Sulggi A.; Telwatte, Sushama; Hatano, Hiroyu; Kashuba, Angela D.M.; Cottrell, Mackenzie L.; Hoh, Rebecca; Liegler, Teri J.; Stephenson, Sophie; Somsouk, Ma; Hunt, Peter W.; Deeks, Steven G.; Yukl, Steven; et al.
Abstract : Background: Most HIV-infected cells during antiretroviral therapy (ART) persist in lymphoid tissues. Studies disagree on whether suboptimal tissue ART concentrations contribute to ongoing HIV replication during viral suppression. Methods: We performed a cross-sectional study in virally-suppressed HIV+ participants measuring lymphoid tissue ART [darunavir (DRV), atazanavir (ATV), and raltegravir (RAL)] concentrations by LC-MS/MS assay. Tissue and plasma ART concentrations were used to estimate TPRs and drug-specific tissue:inhibitory concentration ratios (TICs). HIV DNA and sequentially produced HIV RNA transcripts were quantified from rectal biopsies using droplet digital PCR (ddPCR) assays. Results: Tissue samples were collected in duplicate from 19 participants: 38 rectal, 8 ileal (4 RAL, 2 DRV, 2 ATV), and 6 lymph node (4 RAL, 2 DRV) samples. Overall, median TICs were higher for RAL than DRV or ATV (both P = 0.006). Median TICs were lower in lymph nodes vs. ileum (0.49 vs. 143, P = 0.028) or rectum (33, P = 0.019), and all ART levels were below target concentrations. Higher rectal TICs were associated with lower HIV RNA transcripts (read-through, long LTR, and Nef, P all < 0.026) and a lower long LTR RNA/long LTR DNA ratio ( P = 0.021). Conclusions: We observed higher tissue ART concentrations in ileum and rectum compared with lymph nodes. We observed higher HIV transcription in participants with lower rectal ART concentrations. These findings add to the limited data supporting the idea that viral transcription may be influenced by ART concentrations in lymphoid tissues. Further exploration of tissue pharmacokinetics is needed in future HIV eradication strategies. Abstract : Supplemental Digital Content is Available in the Text.